Application of the Simplex Method to Create A Weekly Menu Planner - Hadzhikolev Emil; Hadzhikoleva Stanka (Acta Universitatis Cibiniensis. Series E: Food Technology, 2018)
Organized meals for different groups - students, servicemen, employees working in specific businesses and organization of work - is invariably care for people’s health. An important task in this process is the preparation of menu plans that correspond to the norms for full, balanced and healthy nutrition for the respective age group and working conditions. They must provide the energy and nutrients necessary for the organism - proteins, carbohydrates, vitamins, fats (of animal and plant origin), etc. In some cases, menu planning must be consistent with the use of available food products or the use of interchangeable or similar foods. Problems arise when it comes to assessment and proving compliance with the quality and quantity standards of the products in the weekly menu plan. A commonly used solution is through the formal substitution of food products from the menu plan with the basic products defined by the norms. The mathematical model we offer creates an optimal solution that leaves minimal quantities of unchanged products.